Running the penultimate lap of the race: A multimethod analysis of growth, generativity, career orientation, and personality amongst men in mid/late career. Issue 2 (30th May 2015) - Arnold, John; Clark, Mike
Abstract : The dynamics of development in mid/late career are relatively uncharted territory in empirical research and represent a point of intersection between work/organizational psychology and lifespan developmental psychology. Using multimethod data from a study of 41 men aged between 45 and 55, we investigated the correlates and compatibility of two key developmental phenomena at this career stage: personal growth and generativity. We found that a forward momentum career orientation (not necessarily in the form of hierarchical advancement) was positively associated with personal growth and generativity, whereas a preoccupation with career maintenance had strong negative relationships with both. However, men's orientation towards their career did not uniquely predict growth or generativity when these variables were also regressed on the personality traits of ego resiliency and ego development, suggesting that personality more than subjective career stage is the root of a positive experience of mid/late career. We also conclude that the importance of personal growth is not confined to the first half of career and that contributing to others (i.e., generativity) is compatible with the ostensibly self‐focused concerns of growth. Differences between findings from self‐report questionnaire and coded interview narratives suggest that method matters in the investigation of these constructs. Practitioner points: Personal growth is relevant to many people in mid–late career. Therefore, it is important not to assume that people at this stage are content to 'coast' towards retirement. Generativity – a desire to contribute to current and future generations – is also important for many workers in mid–late career. It can be expressed in various ways and is not confined to the stereotypical mentoring role. Organizations should therefore facilitate and reward older workers' generative contributions to mainstream activities. A sense of forward momentum in career is associated with growth and generativity. In contrast, a maintenance career orientation (i.e., holding on to prior gains) is associated with less positive results. Discerning a person's career orientation is therefore a quick route to knowing whether they are likely to seek challenges and contribute to the well‐being and development of others at this career stage. Relatively stable personality attributes appear to lie behind both career orientation and growth and generativity in mid–late career. Therefore, it may be difficult to achieve change in the way people approach this part of their career.